SIMULASI SISTEM PERINGATAN DINI KETINGGIAN AIR SUNGAI DENGAN MENGGUNAKAN ALARM DAN SMS GATEWAY BERBASIS AT-MEGA 16 - Firdaus, Muhammad; yuniarto, yuniarto (Gema Teknologi, 2017)
Muhammad Firdaus, Yuniarto, in this paper explain that river is one of the important and supporting places for human life, some uses of the river include supporting industrial activities, tourism and much more, besides that many in some river function sites are used as dams for use as an area of electricity generation or just for control water content, but from rivers also natural disasters can occur, which is like a flood caused by overflowing river water The alert system will flood from overflowing rivers until now it cannot work automatically to determine the river's water level. This causes the average local population not to know when the river surface will overflow. In this study a flood detection system was designed that works automatically by knowing the level (level) of the river's water level In designing this tool, the system will be made on the basis of the Atmega 16 microcontroller, where as an input electrodes will be used as detection of water level, and the output will be an alarm with a certain type of sound that adjusts the water level. destination number in the form of notification of the condition of the river water level to be detected.